PERSONALITY DETERMINANTS OF SMOKING AT THE ELDERLY AGE - Kramchenkova, Vera (PSYCHOLOGICAL JOURNAL, 2016)
The article is devoted to the study of peculiarities of tobacco addictive behavior at the elderly age and personal qualities which condition it. Considering psychological and social aging patterns the elderly age can be viewed as a risk factor for feeling dissatisfaction with oneself, feelings of loneliness, helplessness, anxiety and depression. As smoking is a manifestation of internal imbalance, a compensatory activity of a person done in order to ease psycho-emotional tension, specific character of tobacco addictive behavior at the elderly age is related to age-specific individual features. According to the results of cluster analysis of data on smoking motivation and the level of nicotine addiction, two typological profiles of elderly-aged smokers’ addictive behavior were defined. These profiles are conventionally labelled as “Addictive Type of Smoking” and “Copying Type of Smoking”. An “Addictive Type of Smoking” is characterized by typical addictive behavior with poor control, due to the dominance of tobacco addiction. A “Copying Type of Smoking” is characterized by using smoking primarily as a means of reducing emotional tension and overcoming stress. Specific personality traits of elderly smokers with different types of tobacco addictive behavior were studied. It is has been determined that subjective feeling of loneliness is more evident among smokers of a “Copying Type of Smoking”. Psychoemotional states of smokers with “Addictive Type of Smoking” are characterized by higher indicators of aggressiveness, hypotomia and dysphoria while psychoemotional states of smokers with a “Copying Type of Smoking” are characterized by higher indicators of frustration, anxiety and confusion. Smokers of elderly age, regardless of a smoking type, can be characterized by non-adaptive communicative behavior as to signs of alienation, negativity and subordination to social surrounding. Psychodynamic personality traits, which condition the specific character of communicative style of smokers with an “Addictive Type of Smoking”, are characterized by a higher authoritarianism and criticism and lower conformality and altruism.